(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The rapid development of modern society forces the student to quickly learn and understand the material, especially a foreign language. Nowadays, mastering at least one foreign language is becoming an indispensable requirement for the professional qualification of a specialist. Therefore, it is necessary to pay attention to the efficiency and quality of the process of learning foreign languages. The most effective methods of language learning are interactive methods. The purpose of the article is to determine the main role of interactive methods in teaching English. To achieve the goal, the following tasks were defined: to describe the main interactive methods and to give examples of the use of these methods.